Project feasibility study on rubber basketball - Ang, Nelson; Gavino, Antonio; Meana, Hermenegildo Jr.; Teocson, Alfredo (Diliman, Quezon City College of Engineering, 1978)
The name of our company is BASK-B Manufacturing Corporation. It is to be located in Barrio Rosario (near Green Valley Country Club) in Pasig, Metro Manila. Both the main office and the plant will be located under the same roof. It is the objective of this study to look into industrial ventures wherein part of the country's raw rubber output may be utilized. As it is right now, the raw rubber output exceeds the local demand for it. Basketball is one of the many applications of natural rubber. It is of common knowledge that the popularity of the sport in the country is indeed momentous. Local basketball fans' high enthusiasm for the game gives bright prospect for the overall demand to increase even in the coming years.
Feasibility study
Typescript
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: BASK-B Manufacturing Corporation; Rubber; Basketball; Participatory monitoring and evaluation (Project management)